2015
DOI: 10.5194/isprsarchives-xl-5-w4-53-2015
|View full text |Cite
|
Sign up to set email alerts
|

Structure From Motion Systems for Architectural Heritage. A Survey of the Internal Loggia Courtyard of Palazzo Dei Capitani, Ascoli Piceno, Italy

Abstract: ABSTRACT:We present the results of a point-cloud-based survey deriving from the use of image-based techniques, in particular with multi-image monoscopic digital photogrammetry systems and software, the so-called "structure-from-motion" technique. The aim is to evaluate the advantages and limitations of such procedures in architectural surveying, particularly in conditions that are "at the limit". A particular case study was chosen: the courtyard of Palazzo dei Capitani del Popolo in Ascoli Piceno, Italy, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In contrast, SfM requires neither camera poses nor 3D points to be known prior to scene reconstruction, and it can automatically and simultaneously solves all these unknown parameters from overlapped images (Snavely et al, 2006). The strengths of this technique has been verified and reported in comparison tests with terrestrial laser scanning and in applications of architectural model reconstruction (Ippoliti et al, 2015), landslide monitoring (Chidburee et al, 2016), etc. These merits provide advantages for orientation of oblique UAV images.…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, SfM requires neither camera poses nor 3D points to be known prior to scene reconstruction, and it can automatically and simultaneously solves all these unknown parameters from overlapped images (Snavely et al, 2006). The strengths of this technique has been verified and reported in comparison tests with terrestrial laser scanning and in applications of architectural model reconstruction (Ippoliti et al, 2015), landslide monitoring (Chidburee et al, 2016), etc. These merits provide advantages for orientation of oblique UAV images.…”
Section: Introductionmentioning
confidence: 82%
“…The data distribution revealed that most of the errors were within a range between 5 mm and −5 mm, and that the approach was accurate enough to merge the polygon mesh with the TLS point cloud data. Ippoliti et al [51] studied the conditions of closed spaces to analyse the advantages and limitations of SfM.…”
Section: Related Workmentioning
confidence: 99%
“…Camera calibration was realized automatically during the alignment and identification process of images. The proceedings applied by Agisoft Photoscan Pro have been tested and ensure an excellent calibration of the camera (Ippoliti, Meschini & Sicuranza 2015). This automatic calibration is here applied after verifying the correct coherence between one first photogrammetric model and some reference measurements registered with a laser distance meter.…”
Section: Photogrammetric Surveymentioning
confidence: 99%